Pengaruh Ekstrak Graptophyllum pictum terhadap Pertumbuhan Candida albicans pada Plat Gigi Tiruan Resin Akrilik - Endang Wahyuningtyas (Faculty of Dentistry, Universitas Indonesia, 2012)
Graptophyllum pictum (Daun ungu) is one of the traditional plants in Indonesia. Graptophyllum pictum composition is flavonoid, Flavonoid has an antimicrobial effect. The purpose of this study is to find the effect of Graptophyllum pictum extract prevent the growth of Candida albicans on acrylic resin denture plate. The research was done plaque smear which Candida albicans adhered at the patient denture, then it was cultured and Candida albicans growth was cultivated. The research was done by using 40 samples. The samples were heat cured acrylic resin discs with 10 mm diameter. The research was used dilution method. The samples were divided into four groups.. Each group had been given Graptophyllum pictum extract with 5%, 10%, 20% and 40% for 8 hours. The plates with Sabouraud agar were incubated at 37oC for 24 hours and then Candida albicans were counted. The data were analyzed by the One way variant analysis and t-test. The result showed there were significant differences among the amount of Candida albicans which grew in different concentration of Graptophyllum pictum extract (p < 0.05). The conclusion was that Graptophyllum pictum extract had prevented the growth of Candida albicans on acrylic resin denture plate. DOI: 10.14693/jdi.v15i3.24